Love remains : a Hope Springs novel - Eden, Sarah M. (Eden, Sarah M. Hope Springs series, 2017)
For nearly a year, Tavish O'Connor has carried the crushing weight of his family's future on his shoulders. He has taken on the care of his youngest brother, Finbarr, who lost his eyesight in a terrible accident. As a tutor to the newly blind, Cecily Attwater has dedicated her life to helping others overcome the obstacles she herself has conquered. Her new assignment in a remote corner of Wyoming proves trickier than usual: Finbarr refuses to learn. To make matters worse, his family and the other Irish townspeople are less than thrilled to discover an Englishwoman in their haven. For Finbarr's sake, Tavish and Cecily forge an uneasy alliance that, as the weeks pass, moves toward something deeper.